Karakteristik Fisikokimia Tepung Sorgum (Sorghum bicolor L.) Varietas Lokal Merah dengan Fermentasi Spontan - Syarifah Yusra; Elisa Putri (JURNAL AGROTEKNOLOGI, 2022)
Modification of flour was carried out to improve the functional properties of starch and to expand the use of starch in food products. Local red varieties of sorghum (Sorghum bicolor L.) were modified by spontaneous fermentation to increase protein digestibility and carbohydrate digestibility. In this study, 2 stages were carried out, i.e. natural sorghum flour (TSA), and spontaneously fermented sorghum flour (TSFS) with 3 levels of fermentation times (12, 48, and 72 hours TSFS). The purpose of this study was to determine the physicochemical characteristics of local red sorghum flour using the spontaneous fermentation method. The resulting product was observed for amylose content, tannin content, color, and amylograph profile with a rapid visco analyzer (RVA). The results showed that the fermentation conditions with 72 hours of TSFS increased the highest amylose content (6.43% wb) followed by the greatest change in the amylograph profile of the peak viscosity (2621 cP) compared to the 12 hours of TSFS and 48 hours of TFSF. This correlated positively with a significant decrease in tannin content in the 72-hour TSFS treatment (7.53 mg as.tannat/g). The tannin content lost by this method reached 60% of sorghum flour without treatment (16.69 mg as.tannat/g). However, in the analysis of the brightness level of sorghum flour, it was shown that the brightest color was obtained in the 48 h TSFS treatment. Modification of sorghum flour by spontaneous fermentation (using aquades immersion) can increase starch degradation and effectively improve the physicochemical properties of local varieties of red sorghum flour. Keywords: fermentation, flour, modification, sorghum